Improving prescribing, junior doctor efficiency and confi dence in the acute management of patients following primary percutaneous coronary intervention using a bespoke clerking pro forma. (2019) - Easaw, Jonathan; Shaunak, Ravi; Hammersley, Daniel; Achan, Vinod
No abstract available